Thu nhận ôxít đất hiếm từ quặng Yên Phú - Đặng, Vũ Minh (2011)
Tác giả: Đặng Vũ Minh, GS-TSKH; Lưu Minh Đại, PGS-TS; Đỗ Kim Chung, PGS-TS; Nguyễn Văn Hạnh, KS; Nguyễn Văn Mận, KS -- Từ khóa: Đất hiếm; Ôxít đất hiếm